Examining Factors Influencing Adults' Repurchase Intentions in Green Restaurants: A Study in Klang Valley - Nur Syaza Aliah Salehuddin; Nurnasrin Awatief Ibrahim; Norhaya Hanum Mohamad; Nur Amanina Idris; Antonius Rizki Krisnadi (Information Management and Business Review, 2025)
Green restaurants are establishments that prioritize environmental sustainability by implementing practices such as reducing energy consumption, minimizing disposable product use, and curbing food waste. This study aims to investigate the factors within a modified Theory of Planned Behavior (TPB) framework that influence repurchase intentions toward green restaurants in the Klang Valley. Specifically, it examines how sustainable attitudes, price perceptions, and subjective norms affect consumer decisions while fostering greater awareness and understanding of green dining practices to promote environmental sustainability. A quantitative approach was adopted, surveying 390 Klang Valley residents with prior experiences at green restaurants. Purposive sampling was used to select participants, and data were collected through a structured questionnaire. The responses were analyzed using descriptive statistics, reliability testing, and multiple regression analysis via the Statistical Package for Social Science (SPSS). The findings revealed that all TPB variables, sustainable attitudes, price, and subjective norms, positively influence repurchase intentions, with sustainable attitude emerging as the most significant predictor. These results underscore the importance of fostering pro-environmental attitudes to drive consumer loyalty toward green restaurants. This study contributes to the limited body of research on green restaurants in Malaysia, offering practical insights for restaurant owners, policymakers, and community groups to integrate eco-friendly practices such as reducing paper waste, optimizing energy consumption, and adopting biodegradable disposables. Academically, the study serves as a foundation for future research, encouraging scholars and practitioners to further investigate the potential of green restaurants in advancing environmental sustainability.